Influence of bioactive glass-coating of zirconia implant surfaces on human osteoblast behavior in vitro. Issue 6 (June 2019) - Rohr, Nadja; Nebe, J. Barbara; Schmidli, Fredy; Müller, Petra; Weber, Michael; Fischer, Horst; Fischer, Jens
Highlights: Initial cell behavior of human osteoblasts is not accelerated by the bioactive glass PC-XG3 when compared to zirconia. A decreased surface roughness of zirconia promotes initial cell spreading. Storage of PC-XG3 in cell culture medium induces a corrosion reaction. A coating of zirconia implants with bioactive glass PC-XG3 will unlikely reduce osseointegration time. Abstract: Objective: The recently developed bioactive glass PC-XG3, which is suitable to coat zirconia implant surfaces with high adhesion strength may reduce the time of osseointegration and the marginal bone loss following implantation. The glass composition has been previously evaluated for cytotoxicity on fibroblast cells, and will now be used to evaluate the cell behavior of osteoblast cells. Methods: Three different surface morphologies were created with PC-XG3 on zirconia discs. A clinically tested zirconia implant surface as well as polished and machined zirconia served as a reference. Cell viability after 24 h, cell spreading after 30 min and 24 h and the respective morphology of human osteoblasts using scanning electron microscopy were evaluated. Additionally, the corrosive process of PC-XG3 in cell culture medium up to 7 d was measured. Results: Initial cell behavior of human osteoblasts was not accelerated by the PC-XG3 surface when compared to zirconia. Additionally, it was found that a decreased surface roughness promoted initial cell spreading. Storage in cell culture medium resulted in the accumulation of C and N on the bioglass surface while Mg, Si, K and Ca were decreased and crack formation was observed. Significance: Since initial spreading quality to a biomaterial is a crucial factor that will determine the subsequent cell function, proliferation, differentiation, and viability it can be assumed that a coating of zirconia implants with this bioactive glass will unlikely reduce osseointegration time.